HuD RNA Recognition Motifs Play Distinct Roles in the Formation of a Stable Complex with AU-Rich RNA - Park, Sungmin (American Society for Microbiology, 2000)
Human neuron-specific RNA-binding protein HuD belongs to the family of Hu proteins and consists of two N-terminal RNA recognition motifs (RRM1 and -2), a hinge region, and a C-terminal RRM (RRM3). Hu proteins can bind to AU-rich elements in the 3′ untranslated regions of unstable mRNAs, causing the stabilization of certain transcripts. We have studied the interaction between HuD and prototype mRNA instability elements of the sequence UU(AUUU)(n)AUU using equilibrium methods and real-time kinetics (surface plasmon resonance using a BIACORE). We show that a single molecule of HuD requires at least three AUUU repeats to bind tightly to the RNA. Deletion of RRM1 reduced the K(d) by 2 orders of magnitude and caused a decrease in the association rate and a strong increase in the dissociation rate of the RNA-protein complex, as expected when a critical RNA-binding domain is removed. In contrast, deletion of either RRM2 or -3, which only moderately reduced the affinity, caused marked increases in the association and dissociation rates. The slower binding and stabilization of the complex observed in the presence of all three RRMs suggest that a change in the tertiary structure occurs during binding. The individual RRMs bind poorly to the RNA (RRM1 binds with micromolar affinity, while the affinities of RRM2 and -3 are in the millimolar range). However, the combination of RRM1 and either RRM2 or RRM3 in the context of the protein allows binding with a nanomolar affinity. Thus, the three RRMs appear to cooperate not only to increase the affinity of the interaction but also to stabilize the formed complex. Kinetic effects, similar to those described here, could play a role in RNA binding by many multi-RRM proteins and may influence the competition between proteins for RNA-binding sites and the ability of RNA-bound proteins to be transported intracellularly.